Catalog of technical options for solid waste management in Bangladesh - Majumder, Ayan; Ulrich, Andreas; Taron, Avinandan (CGIAR Research Program on Water, Land and Ecosystems, 2020)
Solid waste management in Bangladesh involves a holistic system that spans waste generation, segregation, collection, transportation, treatment, and final disposal, guided by a well-developed policy and regulatory framework. Emphasis is placed on integrating both centralized and decentralized approaches to accommodate diverse urban conditions. Technological options are adapted to local needs and include anaerobic digestion, refuse-derived fuel (RDF) production, plasma gasification, and material recovery facilities (MRFs), each selected based on waste composition, operational feasibility, and energy recovery potential. Infrastructure innovations such as elevated and underground transfer stations are promoted for their land-use efficiency, reduced environmental impact, and scalability in dense urban settings. Stakeholder involvement is a central pillar, with public–private partnerships (PPPs), NGOs, and the informal recycling sector actively contributing to waste collection, segregation, and material recovery. Behavior change interventions through Information, Education, and Communication (IEC) and Behavior Change Communication (BCC) campaigns are recognized as vital for achieving sustained public participation and source-level waste segregation. Effective planning is supported by robust waste characterization data, which inform site selection, environmental impact mitigation, and post-closure landfill management. Together, these strategies support the development of resilient, inclusive, and environmentally sound SWM systems aligned with long-term sustainability and urban development goals.